VALUE ADDED PRODUCT FROM DIOSCOREA PENTAPHYLLAFLOUR AND RICE FLOUR. (International Journal of Food and Nutritional Sciences, 2022)
In the present scenario, consumers’ preference for intake of healthy products, with high nutraceuticals that prevents or reduces certain diseases such as celiac, diabetes, etc., has been increasing. DioscoreaPentaphylla, which is an underutilized tuber is one such natural rich source of high fiber, and starch with properties like gluten-free and anti-diabetic. The current study was conducted for the development of value-added product like murukkufrom DioscoreaPentaphyllaflour and Rice flour and other minor ingredients. Initially, the dehydrated flour was obtained by tray drying method. Further, using this flour for murukku preparation along with varying combinations of other flours and raw materials. Further, from all the combinations the superior products were selected based on overall acceptance using 9-point hedonic sale with semi-trained panelists and the proximate, organoleptic, shelf life, and microbial properties were analyzed. The results obtained from this study revealed that the dehydrated breadfruit flour (BF) had moisture (6.5±0.10%), protein (9.38±0.15%), fat (0.79±0.25%), carbohydrate (81.56±0.49%) fiber (8.27±0.05%), and ash (2.05±0.09%) and energy 387 kcal. C. Minerals had calcium (mg) 1200±0.06, Magnesium (mg) 623.63 ± 0.02, Manganese (mg) 4.31 ±0.01, Phosporus (mg) 0.63 ±0.01, Sodium (mg) 0.09 ± 0.001 and Selinium (mg) 1.40 ±0.02.